Technical Education Assessment System Based on Fuzzy System - S.S.S., Ahmad; Anwar N.B., M.; Z., Othman; F., Kasmin (International Journal of Human and Technology Interaction (IJHaTI), 2018)
The technical education assessment area offers a ripe ground for some fascinating and testing information mining applications. This application can help both lecturer and student to enhance the nature of education assessment. The capacity to screen the advancement of student's academic performance is a sensitive issue to the scholastic group of higher learning. The present work plans to approach this problem by exploiting fuzzy inference strategy to characterize student scores information as indicated by the level of their execution. In this proposed methodology, we have performed fuzzification of the input data of students marks by making Fuzzy Inference System(FIS) subject insightful, next each FIS yield is gone to next level FIS with two inputs, yields of the last FIS are execution worth computed in view of each coursework marks. Simulation results verify the performance of our proposed fuzzy assessment model for evaluating students’ overall performance.